The Spitzer mid-infrared active galactic nucleus survey. I. Optical and near-infrared spectroscopy of obscured candidates and normal active galactic nuclei selected in the mid-infrared - Lacy, M.; Ridgway, S.; Gates, E.; Nielsen, D.; Petric, A.; Sajina, A.; Urrutia, T.; Cox Drews, S.; Harrison, C.; Seymour, Nick; Storrie-Lombardi, L. (2013)
We present the results of a program of optical and near-infrared spectroscopic follow-up of candidate active galactic nuclei (AGNs) selected in the mid-infrared. This survey selects both normal and obscured AGNs closely matched in luminosity across a wide range, from Seyfert galaxies with bolometric luminosities L bol ~ 1010 L ☉ to highly luminous quasars (L bol ~ 1014 L ☉), all with redshifts ranging from 0 to 4.3. Samples of candidate AGNs were selected with mid-infrared color cuts at several different 24 μm flux density limits to ensure a range of luminosities at a given redshift. The survey consists of 786 candidate AGNs and quasars, of which 672 have spectroscopic redshifts and classifications. Of these, 137 (20%) are type 1 AGNs with blue continua, 294 (44%) are type 2 objects with extinctions AV ~>5 toward their AGNs, 96 (14%) are AGNs with lower extinctions (AV ~ 1), and 145 (22%) have redshifts, but no clear signs of AGN activity in their spectra. Of the survey objects 50% have L bol > 1012 L ☉, in the quasar regime. We present composite spectra for type 2 quasars and objects with no signs of AGN activity in their spectra. We also discuss the mid-infrared—emission-line luminosity correlation and present the results of cross correlations with serendipitous X-ray and radio sources. The results show that: (1) obscured objects dominate the overall AGN population, (2) mid-infrared selected AGN candidates exist which lack AGN signatures in their optical spectra but have AGN-like X-ray or radio counterparts, and (3) X-ray and optical classifications of obscured and unobscured AGNs often differ.